2.9k views
3 votes
Simplify the expression square root of 6 times the square root of 33 plus 7

User Can Lu
by
5.6k points

1 Answer

0 votes

Answer:

3√(22) + 7

Explanation:

The way this is worded can be interpreted two different ways so just to cover the bases, I'll do both. I'm confident they are asking for way 1 though because it wants you to simplify the expression, not evaluate. Way 2 gives you a solution rather than an exact equation.

Number 1

√(6) x √(33) + 7

= √(6 x 33) + 7

= √(198) + 7

= √(9 x 22) + 7

= 3√(22) + 7

Number 2

√(6) x √(33 + 7)

= √(6) x √(40)

= √(6) x (4√(10))

= 4√(60)

= 8√(15)

User Axois
by
5.7k points